Três ensaios sobre a relação dos valores humanos com o bem-estar subjetivo - Uranga, Paulo Ricardo Ricco (2023)
The role of human values is essential for human development, influencing people's orientations and beliefs. The prioritisation of certain values over others can affect the way of life and impact subjective well-being, both positively and negatively. The aim of this thesis was to investigate how this dynamic can be detrimental when people face deprivation and to understand how this relationship manifests in the collective context, considering values and satisfaction in aggregate. The paper is composed of three essays that explored the relationship between human values and subjective well-being. The first essay discussed how deprivation can perpetuate values that sustain situations of injustice, analysing psychological and behavioural phenomena that influence adaptive preferences, and proposing a logical scheme to explain how people endorse values that are detrimental to themselves. The second essay examined how deprivation affects the relationship between values and life satisfaction, finding that people in deprivation tend to be more satisfied by prioritising hedonic and conformity values, while valuing safety may be detrimental to subjective well-being in this condition. In the last essay, which addresses the relationship between values and satisfaction from a regional perspective, it was found that human values have different effects on collective compared to individual satisfaction, highlighting that values of self-transcendence are beneficial for regional satisfaction, while values of self-enhancement may reduce average subjective well-being